UPAYA GURU DALAM MENINGKATKAN KETERAMPILAN KOLABORASI PADA PESERTA DIDIK DI SD NEGERI SUKASARI 4 - Despriyanti, Riska; Hakim, Zerri Rahman; Setiawan, Sigit (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
This research aims to determine teachers' efforts to improve collaboration skills among class VA students at SD Negeri Sukasari 4. The research method applied descriptive research, with research subjects are class VA students. The data collection techniques are techniques, observation and documentation. The analysis technique are interactive analysis techniques with three steps, namely data collection, data reduction, and data verification. The results of this research show that the VA class teacher in his planning; prepares a lesson plan and student worksheets. The implementation includes routine activities, namely the learning process using the Problem Based Learning model, spontaneous activities, namely guiding, monitoring, and also appreciating the results of students' work.Â  The programmed activity is the "Market Day" program. Then students in the VA class have collaboration skills which include good communication and cooperation skills.